Intratumoral therapies and in-situ vaccination for melanoma - Laura A. Huppert; Adil I. Daud (Taylor & Francis Group, 2022)
Skin cancers are among the most physically accessible malignancies, so local delivery of a medication into the tumor, so-called intratumoral therapy, is an appealing route of drug administration. Intratumoral therapies have the potential to increase local drug concentration and/or attract immune cells to the local tumor microenvironment, possibly with fewer systemic side effects. A wide array of intratumoral agents have been studied to date in patients with advanced melanoma, including chemotherapeutic drugs, immune modulating agents, and cancer-directed vaccines. In this review, we will summarize the key pre-clinical and clinical data supporting the use of intratumoral therapy for advanced unresectable and metastatic melanoma. First, we will discuss the history of intratumoral immunotherapy for the treatment of melanoma and the various agents studied to date. Second, we will explore how intratumoral therapies can constitute an in situ vaccine, potentially leading to disease control both locally and systemically. Finally, we will highlight opportunities in the field and key future directions.